2015
DOI: 10.12681/mms.1051
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of fish photobacteriosis. Comparison of the efficacy of intraperitoneally administered commercial and experimental vaccines

Abstract: Two commercial multivalent vaccines against vibriosis, caused by Vibrio anguillarum serotype(s) and photobacteriosis, caused by Photobacterium damsela subsp. piscicida, one with oil adjuvant (AJ) and the other, being an aqueous solution (AV), and an experimental monovalent (Ph. damselae subsp. piscicida) vaccine inactivated with formalin or heat, namely EVF and EVH, were tested in laboratory trials on sea bass (Dicentrarchus labrax) with respect to their efficacy against experimentally induced photobacteriosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(26 reference statements)
2
2
0
3
Order By: Relevance
“…Specific antibodies titres raised against either of the pathogens were significantly higher from the experimental group that was immunized with the adjuvanted commercial vaccine (AJ). This is in agreement with previous studies (Bakopoulos et al , 2015a, b) and the presence of adjuvant has been shown to have a profound effect on the efficacy of adjuvanted vs aqueous formulations (Gravningen et al , 1998; Lund et al , 2003; Nikoskelainen et al , 2007; Bakopoulos et al , 2015a). This effect is due to stimulation of non-specific immune factors; it has been shown adjuvants induce a strong attraction of different types of leukocytes in the area of vaccination and can have a prolonged effect due to slower release of antigen (Afonso et al , 2005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specific antibodies titres raised against either of the pathogens were significantly higher from the experimental group that was immunized with the adjuvanted commercial vaccine (AJ). This is in agreement with previous studies (Bakopoulos et al , 2015a, b) and the presence of adjuvant has been shown to have a profound effect on the efficacy of adjuvanted vs aqueous formulations (Gravningen et al , 1998; Lund et al , 2003; Nikoskelainen et al , 2007; Bakopoulos et al , 2015a). This effect is due to stimulation of non-specific immune factors; it has been shown adjuvants induce a strong attraction of different types of leukocytes in the area of vaccination and can have a prolonged effect due to slower release of antigen (Afonso et al , 2005).…”
Section: Discussionsupporting
confidence: 92%
“…More information cannot be provided because of its proprietary nature. The efficacy of both these products against infection with Phdp has been described before (Bakopoulos et al , 2015a) and field data support the efficacy of both products against Vibriosis. Both these products were purchased and kindly donated by the company Cephalonian Aquaculture for the purposes of this study.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…Caution should be given therefore for the possible transmission of the pathogen among different Mediterranean farmed species. Commercially available vaccines against Photobacteriosis have been available for quite some time for farmed gilthead seabream and European seabass (Bakopoulos et al, 2015) and effective chemotherapy exists to confront the bacterium (Rigos & Troisi, 2005).…”
Section: Bacteriamentioning
confidence: 99%
“…, ενώ η προστασία που παρέχεται μετά τον εμβολιασμό κατά του Phdp είναι αμφισβητήσιμη . (Gravningen et al 2008) και για διδύναμα εμβόλια σε λαβράκι (Bakopoulos et al 2015b). Στα πειράματα που έγιναν στην παρούσα μελέτη, η σοβαρότητα της λοίμωξης όπως αποδείχθηκε από την ποσοστιαία αθροιστική θνησιμότητα των μη εμβολιασμένων ψαριών (μαρτύρων), επηρέασαν τις τιμές RPS που υπολογίστηκε και στις δύο περιπτώσεις και για τα δύο εμβόλια.…”
Section: ειδικός ρυθμός αύξησης (Sgr) και συντελεστής μετατρεψιμότητας τροφής (Fcr)unclassified